2016
DOI: 10.1093/femsec/fiw158
|View full text |Cite
|
Sign up to set email alerts
|

The fungal endophyteChaetomium globosumnegatively affects both above- and belowground herbivores in cotton

Abstract: Mutualistic plant-endophyte symbioses can benefit plants by increasing host fitness through reductions in herbivory. The fungus, Chaetomium globosum strain TAMU 520, was previously isolated as an endophyte from cotton (Gossypium hirsutum) and can be re-inoculated to systemically colonize cotton plants via seed treatment. We evaluated the potential impacts of the endophyte in cotton on plant parasitic nematodes belowground, along with piercing-sucking and chewing insects aboveground. Endophytic C. globosum inhi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
38
0
6

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 49 publications
(48 citation statements)
references
References 58 publications
4
38
0
6
Order By: Relevance
“…The use of beneficial fungi associated with plants that may confer increased resistance or tolerance to nematodes could provide an alternative to chemical applications for their control (Cabanillas et al 1988;Hallmann and Sikora 1996;Latch 1993;Martinez-Beringola et al 2013;Mendoza and Sikora 2009;Tian et al 2014;Waweru et al 2013). Certain beneficial strains of Fusarium spp., Pochonia chlamydosporia, Phialemonium inflatum, Piriformospora indica, and Chaetomium globosum, have been reported to have antagonistic effects on nematodes while being present in plants as endophytes (Bajaj et al 2015;Larriba et al 2015;Martinuz et al 2015;Yan et al 2011;Zhou et al 2016;Zhou et al 2018).…”
mentioning
confidence: 99%
“…The use of beneficial fungi associated with plants that may confer increased resistance or tolerance to nematodes could provide an alternative to chemical applications for their control (Cabanillas et al 1988;Hallmann and Sikora 1996;Latch 1993;Martinez-Beringola et al 2013;Mendoza and Sikora 2009;Tian et al 2014;Waweru et al 2013). Certain beneficial strains of Fusarium spp., Pochonia chlamydosporia, Phialemonium inflatum, Piriformospora indica, and Chaetomium globosum, have been reported to have antagonistic effects on nematodes while being present in plants as endophytes (Bajaj et al 2015;Larriba et al 2015;Martinuz et al 2015;Yan et al 2011;Zhou et al 2016;Zhou et al 2018).…”
mentioning
confidence: 99%
“…and Chaetomium cochliodes Palliser were collected from two survey sites. Zhou et al (2016) reported that C. glabosum strain TAMU 520 inhibited rootknot nematode (Meloidogyne incognita (Kofold & White) Chitwood) infection and reduced female reproduction on cotton roots. Aboveground, endophytic C. globosum reduced the fecundity of both cotton aphid, Aphis gossypii Glover, and beet armyworm, Spodoptera exigua (H€ ubner).…”
Section: Resultsmentioning
confidence: 99%
“…We also detected occasional colonization of untreated control plants by the target endophytes, but do not know if these rare events were due to contamination prior to planting or naturally occurring colonization during subsequent plant growth. Overall, our colonization and insect behavioral findings are consistent with previous studies using these same isolates that have demonstrated endophytic colonization of cotton along with associated treatment effects on cotton aphid ( Aphis gossypium ), cotton bollworm ( Helicoverpa zea ) and root‐knot nematode ( Meloidogyne incognita ) performance and reproduction, as well as plant growth (Lopez et al ., ; Lopez & Sword, ; Zhou et al ., ,b).…”
Section: Discussionmentioning
confidence: 99%
“…Although largely ignored until recently (Porras‐Alfaro & Bayman, ; Wani et al ., ), a growing number of studies demonstrate that the presence of these facultative endophytes in the plant can be manipulated in both mono‐ and dicots through the targeted inoculation of candidate fungi. These endophyte‐colonized plants can negatively affect the performance and survival of a range of both above‐ and below‐ground herbivores (e.g., Gurulingappa et al ., ; Hernawati et al ., ; Akello & Sikora, ; Menjivar et al ., ; Gange et al ., ; Martinuz et al ., ; Thakur et al ., ; Akutse et al ., ; Batta, ; Lopez et al ., ; Lopez & Sword, ; Zhou et al ., ,b). Facultative fungal endophytes can also be involved in nutrient transfer to plants, and positively affect plant growth, thereby potentially serving as multifaceted tools for plant protection and health in agricultural systems (Behie et al ., ; Behie & Bidochka, ; Barelli et al ., ; Jaber & Enkerli, ; Lugtenberg et al ., ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation